Bioavailability of iron, vitamin A, zinc, and folic acid when added to condiments and seasonings. Issue 1 (15th October 2015) - Degerud, Eirik M.; Manger, Mari Skar; Strand, Tor A.; Dierkes, Jutta
Abstract : Seasonings and condiments can be candidate vehicles for micronutrient fortification if consumed consistently and if dietary practices ensure bioavailability of the nutrient. In this review, we identify factors that may affect the bioavailability of iron, vitamin A, zinc, and folic acid when added to seasonings and condiments and evaluate their effects on micronutrient status. We take into consideration the chemical and physical properties of different forms of the micronutrients, the influence of the physical and chemical properties of foods and meals to which fortified seasonings and condiments are typically added, and interactions between micronutrients and the physiological and nutritional status of the target population. Bioavailable fortificants of iron have been developed for use in dry or fluid vehicles. For example, sodium iron ethylenediaminetetraacetic acid (NaFeEDTA) and ferrous sulfate with citric acid are options for iron fortification of fish and soy sauce. Furthermore, NaFeEDTA, microencapsulated ferrous fumarate, and micronized elemental iron are potential fortificants in curry powder and salt. Dry forms of retinyl acetate or palmitate are bioavailable fortificants of vitamin A in dry candidate vehicles, but there are no published studies of these fortificants in fluid vehicles. Studies of zinc and folic acid bioavailability in seasonings and condiments are also lacking.